Indigenous Spirits and Global Aspirations in a Southeast Asian Borderland : Timor-Leste's Oecussi Enclave - Rose, Michael (Book collections on Project MUSE., 2020)
Over the past 40 years, life in Timor-Leste has changed radically. Before 1975 most of the population lived in highland villages, spoke local languages, and rarely used money. Today many have moved to peri-urban lowland settlements, and even those whose lives remain dominated by customary ways understand that those of their children will not. For the Atoni Pah Meto of the island's west, the world was neatly divided into two distinct categories: the meto (indigenous), and the kase (foreign). Now things are less clear; the good things of the outside world are pursued not through rejecting the meto ways of the village, or collapsing them into the kase, but through continual crossing between them. In this way, the people of Oecussi are able to identify in the struggles of lowland life, the comforting and often decisive presence of familiar highland spirits.